Comparison of the gut microbiota and metabolism in different regions of Red Swamp Crayfish (Procambarus clarkii) - Songyi Liu; Songyi Liu; Ziyan Wang; Ziyan Wang; Ze Wang; Ze Wang; Qiaoli Wu; Qiaoli Wu; Jun Zhou; Jun Zhou; Rixin Wang; Rixin Wang; et al. (Frontiers in Microbiology, 2023)
BackgroundThe gut microbiota is very important for maintaining the homeostasis and health of crustaceans. Many factors affect the gut microbiota of crustaceans, one of which is temperature. However, it is currently unclear how temperature affects the gut microbiota and metabolites of Procambarus clarkii.MethodsUsing metagenomic sequencing and gas chromatography–mass spectrometry (GC–MS) techniques, the gut microbiota and metabolites of P. clarkii from Hubei (HB), Jiangsu (JS), Shandong (SD), and Zhejiang (ZJ) in China were investigated.ResultsUnder the impact of temperature, the gut microbiota and metabolites of P. clarkii exhibit a specific trend of change. The primary pathogenic bacteria affecting P. clarkii are Citrobacter, Enterobacterium, and Aeromonas, which are affected by temperature. Two metabolites, namely, sugars and amino acids, are regulated by temperature.ImplicationThis study demonstrated that the gut microbiota and gut metabolites of P. clarkii were considerably affected by temperature. It provides a theoretical basis for the systematic study of P. clarkii and provides a basis for a healthy culture of P. clarkii.